Acland's DVD atlas of human anatomy - Acland, Robert D.; Lippincott Williams & Wilkins (Baltimore : Lippincott Williams & Wilkins, 2004)
Shows dissections, in 3-dimensional views, of unembalmed human bodies
The upper extremity (v.1) -- The lower extremity (v.2) -- The trunk (v.3) -- The head and neck, part 1 (v.4) -- The head and neck, part 2 (v.5) -- The internal organs --(v.6)
System requirements : Either a consumer-grade DVD player or PC capable of playing DVDs
Keywords: Anatomy; Dissection